Analisis validasi student worksheet dalam model inkuiri terbimbing berorientasi high order thinking skill (HOTS) pada materi dinamika rotasi dan elastisitas di kelas XI SMA/MA - Prima Nora Ananda; Yenni Darvina; Silvi Yulia Sari (Universitas Negeri Padang, 2019)
21st century requires students be able to learn independently, use higher-order thinking skills, find information and have good competence. For this demand the government has made improvements to the 2013 revised 2017 curriculum. The curriculum contains four points, namely strengthening of character education (PPK), 4C skills, Literacy and Higher Order Thinking Skills (HOTS). The focus of the discussion is Higher Order Thinking Skills. HOTS consists of 4 indicators namely critical thinking, creative thinking, decision making and problem solving. Actually not all students can find information without guidance. The learning model fits the indicators mentioned is the guided inquiry. In applying the guided inquiry, it will be maximized if supported by Student Worksheets. Through Student Worksheet teachers and students will easier to carry out learning. HOTS-oriented Student Worksheets in the guided inquiry model have several advantages. First, it is not used for practical work only but can be used to guide activities during class learning. Because there are clear learning instructions for teachers and students. Second, it can improve students' HOTS abilities, because they are oriented with HOTS indicators. Third, it can improve students' ability to collect information independently because the model used is guided inquiry. The type of research used is Research and Development (R&D). The R & D research method is a research method used to produce certain products. The validity and practicality values of the HOTS-oriented Student Worksheet in the guided inquiry model are 81,78% and 94,75% according to the teacher and 85,92% according to the student.